Participant Observation: A Proposed Method to Study the Influence of Actual Social Ties in the Formation of Trust towards Social Commerce in Malaysia - Sabrina Abdul Rahim, Mohd Khairudin Kasiran, Mazida Ahmad (International Journal of Advanced Science and Technology, 2020)
Existing studies have mostly employed a survey method to study relationship between trust and intention to purchase in social commerce. This method is relying on self-reported data from respondents where verifying the accuracy of data is quite challenging. While a participant observation method is still scarce method used in the previous studies, this study is intended to identify the suitable and simple activities in conducting the participant observation to investigate the influence of actual social ties existed between consumers and individual online seller to trust and purchase in Consumer-to Consumer (C2C) Social Commerce. A review of literatures on participant observation method is conducted to identify an appropriate processes or activities for this study. These activities will help researcher to execute a proper participant observation method in acquiring and analyzing more accurate data and hence producing higher validity findings on trust in C2C social commerce study. The participant observation method however, could distract researcher’s objectivity and prolong the duration of the study. Therefore, the usage of this method will need to be planned extra carefully before applying it in a real study. Keywords: trust, C2C social commerce, participant observation method.